The Impact of Risk Management on Banks’ Profitability: A South African Perspective - Razermera, Tsitohaina; Brijlal, Pradeep; Jwara, Nomthandazo (International Journal of Economics and Financial Issues, 2024)
Global research has shown that different risk management practices in banks and companies, in general, may significantly influence their profitability. This research paper investigates the impact of credit risk, liquidity risk and market risk in the banking sector in South Africa. It adds to the literature by improving the existing models and by exploring the impact of the coronavirus on the profitability of the same banks through the lens of risk management. The research used quantitative data collected from the six largest commercial banks in South Africa during the period (2013-2020),before Covid-19. Several panel regression models were developed to incorporate credit, liquidity, and market risks. The results showed that the primary determinant of bank profitability was the management of non-performing loans, implying that other financial risks may already be appropriately managed or diversified away in the South African context. However, banks and regulators should place more importance on evaluating the creditworthiness of their current and prospective customers.